2023
DOI: 10.1002/2688-8319.12244
|View full text |Cite
|
Sign up to set email alerts
|

Restore or rewild? Implementing complementary approaches to bend the curve on biodiversity loss

Abstract: Biodiversity loss and climate change are arguably the most pressing challenges of our time, each intimately and inextricably linked with human well-being and the future of the living world. These two major environmental crises are fundamentally connected, not only in terms of the driving processes, feedback and mechanistic links, but, critically, also in terms of potential solutions (Pettorelli et al., 2021). Nature recovery, in particular, has gained significant traction in recent years as a solution to joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The biodiversity and climate crises can be jointly addressed by integrating restoration and rewilding approaches, capitalizing on their strength and targeting different socioecological contexts [25]. The multifaceted field of restoration ecology is reflected by various and broad definitions of restoration [12], as they were given by the Society of Ecological Restoration, the UN Decade on Ecosystem Restoration, and the IUCN.…”
Section: Rewilding In European Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…The biodiversity and climate crises can be jointly addressed by integrating restoration and rewilding approaches, capitalizing on their strength and targeting different socioecological contexts [25]. The multifaceted field of restoration ecology is reflected by various and broad definitions of restoration [12], as they were given by the Society of Ecological Restoration, the UN Decade on Ecosystem Restoration, and the IUCN.…”
Section: Rewilding In European Contextmentioning
confidence: 99%
“…The multifaceted field of restoration ecology is reflected by various and broad definitions of restoration [12], as they were given by the Society of Ecological Restoration, the UN Decade on Ecosystem Restoration, and the IUCN. If restoration is recognized in mainstream conservation and policy, rewilding is viewed as an alternative way to achieve the large-scale recovery of nature [25]. In the opinion of Shackelford and McDougall [12], rewilding is a branch of restoration-related practice that has experienced a surge in the last few decades.…”
Section: Rewilding In European Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Rewilding is often expected to require large areas of land (Pettorelli & Bullock, 2023; but see e.g. Mills et al, 2017), and thus projects are commonly found in high elevation, high latitude, remote areas (Jepson et al, 2018), as is the case for protected areas in general (Joppa & Pfaff, 2009).…”
Section: Introductionmentioning
confidence: 99%